Media use and psychosocial adjustment in children and adolescents - Nicha Limtrakul (2018)
© 2017 Paediatrics and Child Health Division (Royal Australasian College of Physicians). Aims: Currently, television and new forms of media are readily available to children and adolescents in their daily lives. Excessive use of media can lead to negative physical and psychosocial health effects. This study aimed to describe children's media use, including media multitasking, as well as the associations between media use and their psychosocial adjustment. Methods: This study recruited 339 participants aged 10-15 years from an international school. The children and their care givers were asked to complete the Strengths and Difficulties Questionnaire independently to evaluate the psychosocial problems of the children. Results: The mean age of the study participants was 12.4±1.5years, who were recruited from grades 5 to 9. Multitasking media use was reported in 59.3% of participants. The average total media exposure time was 7.0h/day. The behavioural problem scores from self-reports were greater with increased media use time. After adjusting for confounding variables, the school report and sleep problems were among the factors associated with the total behavioural problem scores from the multiple linear regression analysis (P=0.001 and < 0.001, respectively), whereas age and average total media exposure time were significantly associated with the prosocial behaviour scores reported by the children (P=0.004 and 0.02, respectively). Multitasking media use was not significantly associated with the total difficulties scores or the prosocial behaviour scores in this study. Conclusion: Increased media use time was significantly associated with decreased prosocial behaviour scores in children in this study. This can provide important information to parents regarding media use in children.